Umpiring Technology and Tactical and Strategic Privacy in Cricket - DC, Suman (Unity Journal, 2023)
Each sport has an allotted area for innovative tactics and strategies, while some sports go beyond the sporting rules and regulations. The use of present-day technologies in sports has helped teams and management better understand their rivals’ strategies and tactics through tactical and strategic analysis, and the teams always look for such type of resources to prepare their teams accordingly. The use of sports technology at various levels, from training to officiating a match, itself might reveal a team’s tactics and strategies to its opponents and to a greater group, which could influence the team’s plan and the way it has been executed. For an instance, different umpiring technologies are used in the sports like cricket to execute the game in a fair manner. Imagine a scenario where umpiring technology invades the privacy of the players' tactics and strategies by disclosing them while officiating the game. In the meantime, the implementation of umpiring technology has not been investigated from the perspective of athletes’ tactical and strategic privacy. Therefore, this research paper aims to investigate the dimensions of umpiring technology in sports in relation to strategic and tactical privacy and to imply how the responsible uses of sports technology can be made for the betterment of overall sports. In the process, this research investigates concepts of strategy, tactics, and privacy in relation to pertinent ideas like gamesmanship in sports. Following that, these concepts are applied in a couple of cases in international cricket matches, demonstrating whether the sports technology can reveal a team’s tactical and strategic privacy to various parties. In a broader sense, this research can assist individuals in comprehending various aspects of using sports technology responsibly.